Dual Negative Differential of Heat Generation in a Strongly Correlated Quantum Dot Side-Coupled to Majorana Bound States - Wang, Zhu-Hua; Huang, Wen-Cheng (Frontiers in Physics, 2021)
We study theoretically the properties of local heat originated from energy exchange between electrons passing through a quantum dot (QD) coupled to a phonon bath. The dot is sandwiched between two normal metal leads and also side-coupled to Majorana bound states (MBSs) formed at opposite ends of a topological superconductor nanowire. We find that in addition to the negative differential of heat generation (NDHG) in the Coulomb blockade regime, another NDHG emerges near the leads' Fermi level due to the dot-MBS coupling. This dual NDHG effect is robust against the variation of intradot Coulomb interaction strength, and disappears if the QD is coupled to regular Fermions. Direct hybridization between the MBSs reduces their impacts on the electronic transport processes, and eliminates the dual NDHG effect. Our results show that the dual NDHG effect is quite efficiency for inferring the existence of MBSs, and may remedy some limitations of the detection schemes relying on tunneling spectroscopy technique.